Potential of spiral breast computed tomography to increase patient comfort compared to DM - Wetzl, Matthias; Wenkel, Evelyn; Dietzel, Matthias; Siegler, Lisa; Emons, Julius; Dethlefsen, Ebba; Heindl, Felix; Kuhl, Christiane; Uder, Michael; Ohlmeyer, Sabine (European Journal of Radiology, 2021)
Purpose: To intra-individually compare patient comfort of spiral breast computed tomography (SBCT) versus digital mammography (DM).
CRIS-Team WoS Importer:2022-02-04